Pengembangan Aplikasi Penjualan Tiket Acara Berbasis Website dan Mobile - Muhammad Abdurrasyid Nugroho; Muhammad Fachrie (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research presents innovation in the form of web-based and mobile event ticket sales applications using the PHP and Kotlin programming languages. The goal is to provide convenience to users in booking event tickets and registering events themselves from their homes. The application is designed to simplify the ticket booking process, improve accessibility, and provide an optimal user experience. Key features include a responsive user interface, being able to register new events, book desired events, view booked events, view registered events. By combining the advantages of PHP and Kotlin programming languages, this research has the potential to provide a more efficient and satisfying event ticket booking and sales experience for users.